A Blueprint for Evidence-Based Practice? Assessing the Warnock Inquiry's Proposals for Research and Development in Special Education 40 Years On - Webster, Rob (Frontiers in Education, 2019)
In just seven of its almost 400 pages, the Warnock Report set out an ambitious programme for research and development in special education. The Committee not only identified areas in need of further investigation, revealed via the Inquiry process, but went beyond this, with recommendations designed to improve teachers' involvement in and engagement with research, and the processes of translating research into practical tools and strategies for practitioners in schools and classrooms. Warnock's vision reimagined academic roles as being more applied and in-touch with practice on the ground, created spaces for teachers to contribute to and conduct research, and suggested an elementary architecture for a coordinated, and more democratized approach to research in special education. This paper explores the development of some of the Warnock Inquiry's key proposals on research and development in special education. In the first half of this paper, we consider how the progress made to improving teachers' relationship with research and usage of research findings. It is suggested that much of what has emerged in the UK in recent years regarding the principles and mechanisms for moving the mainstream teaching profession to adopting evidence-based practices are prefigured in the Inquiry report. The second half of the paper revisits the Committee's research priorities and describes how the specific proposals relating to improving school-based research were addressed. We then consider the research priorities of today, and in particular, how “big data” might be harnessed to improve our understanding and knowledge of the impacts of the more inclusive, less segregated, approaches to schooling that the Warnock Committee precipitated.